Antioxidant and antiaging activity of rutin and caffeic acid - Ermi Girsang; I Nyoman Ehrich Lister; Chrismis Novalinda Ginting; Ika Adhani Sholihah; Martinus Ahmad Raif; Sidharta Kunardi; Hendy Million; Wahyu Widowati (Pharmaciana, 2020)
Aging is a complicated process occurring due to the combination of incremental alterations of the skin and accumulated extrinsic factors that causes both structural and functional disruptions. The extrinsic factor of skin aging is mostly caused by free radicals, UV exposures, and pollution. Prevention is possible by escalating antioxidant intake to scavenge ROS in the skin aging process. Rutin and caffeic acid are recognized for their free radical trapping effects and reported to have potential antiaging activities. This study aimed to identify the potentials of rutin and caffeic acid as antioxidant and antiaging. Rutin and caffeic acid were tested for their antioxidant properties using the DPPH, H2O2, ABTS radical scavenging, and FRAP assays. Meanwhile, their antiaging activities were examined by collagenase, elastase, hyaluronidase, and tyrosinase inhibitory assays. The study drew on the evidence of antioxidant and antiaging properties from the scavenging, ferric ion reducing, and inhibitory activities of rutin and caffeic acid (in ascending order): in scavenging DPPH free radicals (IC50 of rutin = 5.79 µg/mL, IC50 of caffeic acid = 8.72 µg/mL), scavenging H2O2 ( IC50 rutin = 12.09 µg/ml, IC50 caffeic acid = 15.23 µg/mL), reducing ABTS (IC50 caffeic acid = 6.23 µg/mL, IC50 rutin = 16.59 µg/mL), reducing ferric ions at 50 µg/mL (FRAP of rutin = 480.08 µM Fe(II)/µg, FRAP of caffeic acid= 526.50 µM Fe(II)/µg), inhibiting collagenase (IC50 caffeic acid = 74.42 µg/mL, IC50 rutin = 104.70 µg/mL), inhibiting elastase (IC50 rutin = 46.88 µg/mL, IC50 caffeic acid = 76.95 µg/mL), inhibiting tyrosinase (IC50 rutin = 55.65 µg/mL, IC50 caffeic acid = 145.91 µg/mL), and inhibiting hyaluronidase (IC50 rutin = 114.07 µg/mL, IC50 caffeic acid= 244.45 µg/mL). Rutin and caffeic acid have the potentials as antiaging and antioxidant.